Analisis Literatur Strategi Handover pada Infrastruktur Telekomunikasi Berbasis Multi-Radio Access Technology - Zahra Haiva Meydina; Yulindon Yulindon (Kampus Akademik Publiser, 2026)
The evolution of telecommunication networks toward 5G and Beyond 5G (B5G)/6G introduces new challenges in mobility management, particularly in the handover process within Multi-Radio Access Technology (Multi-RAT) environments. This study aims to comprehensively analyze handover strategies developed for heterogeneous networks. The method employed is a Systematic Literature Review (SLR) using the PRISMA approach on reputable international journal publications from 2020 to 2026. The results indicate that AI/ML-based methods are capable of reducing latency by approximately 30–50% and decreasing handover failure by 40–60% compared to traditional methods. In addition, hybrid approaches demonstrate improved performance with latency reductions of up to 50–70%, while dual connectivity is able to reduce handover interruption time by more than 95% and decrease latency by approximately 50%. MEC-based approaches have also been proven to improve network efficiency through latency reductions of around 20–40%.